2008
DOI: 10.1371/journal.pone.0001577
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of the Impact of STRICTA and CONSORT Recommendations on Quality of Reporting for Acupuncture Trials

Abstract: BackgroundWe investigated whether there had been an improvement in quality of reporting for randomised controlled trials of acupuncture since the publication of the STRICTA and CONSORT statements. We conducted a before-and-after study, comparing ratings for quality of reporting following the publication of both STRICTA and CONSORT recommendations.Methodology and Principal FindingsNinety peer reviewed journal articles reporting the results of acupuncture trials were selected at random from a wider sample frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 22 publications
9
136
1
4
Order By: Relevance
“…Similarly, Prady et al found that more recent studies of acupuncture tended to have better reporting than older studies. 2 Our study found that overall, the quality of reporting was improved for studies published after 2003 compared to those published before 1994. However, there were very few individual guideline items that were clearly reported more frequently in the late study group compared to the early study group; this is most likely due to the low number of publications available for this study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, Prady et al found that more recent studies of acupuncture tended to have better reporting than older studies. 2 Our study found that overall, the quality of reporting was improved for studies published after 2003 compared to those published before 1994. However, there were very few individual guideline items that were clearly reported more frequently in the late study group compared to the early study group; this is most likely due to the low number of publications available for this study.…”
Section: Discussionmentioning
confidence: 65%
“…For our current study, these data were entered into an excel spreadsheet by a trained data extractor and checked for accuracy by a second extractor. We used the STRICTA and CONSORT assessment checklists devised by Prady et al 2 as guides for our data extraction (table 1). For elements of the checklists that were not included in our previous abstraction, we returned to the original publication to com- plete all elements of the checklists.…”
Section: Data Collectionmentioning
confidence: 99%
“…Since its appearance, there have been several extensions to CONSORT, intended to adapt their application to (i) specific trial designs, such as cluster trials, N-of-1 trials, pragmatic trials, and pilot and feasibility trials, among others; (ii) specific types of interventions, such as herbal medicinal, nonpharmacological, and acupuncture; (iii) different types of outcomes, such as patientreported outcomes and harms; and (iv) specific formats of trial reports such as abstracts and RCT protocols, all of which can be found in the Enhancing Quality and Transparency of Health Research (EQUATOR) network (9) and on the CONSORT website (10). Some studies have revealed that the use of the CONSORT statement is associated with enhanced quality of reporting of clinical trials and, in particular, that checking submitted manuscripts for missing items from the CONSORT list in peer-review processes can improve the quality of peer reviews and the final publications (11)(12)(13)(14). For example, it was found that peer reviewers failed to detect important deficiencies in reporting of the methods and results of RCTs (15).…”
Section: Lack Of Adherence To Reporting Guidelines For Rctsmentioning
confidence: 99%
“…More subtle characteristics are the level of experience and education of the acupuncturist in question. However, after the publication of "Standards for reporting interventions in controlled trials of acupuncture: the STRICTA recommendations" in 2002, 79 followed by the publication of a collaboration between the Consolidated Standards of Reporting Trials (CONSORT) and the Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA) groups, 80 the reporting of acupuncture trials has become better.…”
Section: Surgery As a Risk Factor For Ponvmentioning
confidence: 99%